PENGARUH PENGGUNAAN MEDIA BONEKA TANGAN TERHADAP KETERAMPILAN BERCERITA SISWA KELAS V SD SE-GUGUS 4 KECAMATAN BANTUL - Siti Mariana; Enny Zubaidah (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2015)
Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media boneka tangan terhadap keterampilan bercerita siswa kelas V SD se-gugus 4 Kecamatan Bantul. Jenis penelitian ini adalah quasi experiment dengan desain pretest-posttest group. Populasi penelitian ini adalah siswa kelas V SD se-gugus 4 Kecamatan Bantul pada semester I tahun ajaran 2013/2014. Sampel dipilih sebanyak tiga kelas dengan menggunakan teknik cluster sampling. Teknik pengumpulan data yang digunakan adalah teknik tes. Instrumen tes divalidasi dengan teknik expert judgement kemudian diujicobakan. Hasil ujicoba dianalisis menggunakan Alpha Cronbach dengan bantuan SPSS versi 16.0 untuk mengetahui reliabilitasnya. Uji normalitas menggunakan Kolmogorov-Smirnov dan uji homogenitas menggunakan Levene Test pada SPSS. Pengujian hipotesis dilakukan menggunakan uji-t. Hasil analisis kemudian diuji signifikansinya dengan taraf signifikansi 0,05.Hasil penelitian ini menunjukkan bahwa skor keterampilan bercerita kelompok kontrol dan kelompok eksperimen I dan II berdistribusi normal dan homogen. Kelompok kontrol memperoleh rata-rata skor pretest 16,07 dan posttest 16,60, kelompok eksperimen I memperoleh rata-rata skor pretest 16,13 dan posttest 20,97, sedangkan kelompok eksperimen II memperoleh skor pretest 15,80 dan posttest 20,90. Hasil uji-t adalah sig. 2 tailed 0,000 0,05. Dari data tersebut dapat disimpulkan bahwa terdapat pengaruh yang signifikan penggunaan media boneka tangan terhadap keterampilan bercerita siswa kelas V SD se-gugus 4 Kecamatan Bantul. Kata Kunci: media boneka tangan, keterampilan bercerita THE EFFECTS OF THE USE OF HAND PUPPETS ON THE STORYTELLING SKILLS OF GRADE V STUDENTS AT ELEMENTARY SCHOOLS IN CLUSTER 4 OF BANTUL DISTRICT. Abstract This study aims to investigate the effects of the use of hand puppet media on the storytelling skills of Grade V students at elementary schools in Cluster 4 of Bantul District. This was a quasi-experimental study employing the pretest-posttest group design. The research population comprised Grade V students at elementary schools in Cluster 4 of Bantul District in semester I in the academic year of 2013/2014. The sample, consisting of three classes, was selected by means of the cluster sampling technique. The data were collected through tests. The tests were administered to investigate students’ story-telling skills before and after the treatment. The test instruments were validated through expert judgment and were then tried out. The results of the tryout were analyzed using the Cronbach Alpha assisted by SPSS Version 16.0 to assess the reliability. The normality was tested by the Kolmogorov-Smirnov test and the homogeneity by the Levene test in SPSS. The hypotheses were tested by the t-test. The significance of the results of the analysis was then tested at a significance level of 0.05.The results of the study showed that the scores of the storytelling skills of the control group, experimental group I, and experimental group II were normally distributed and homogeneous. The control group attained an average pretest score of 16.07 and an average posttest score of 16.60. Experimental group I attained an average pretest score of 16.13 and an average posttest score of 20.97, while experimental group II attained an average pretest score of 15.80 and an average posttest score of 20.90. The result of the t-test was indicated by sig. 2 tailed 0.000 0.005. From the data, it can be concluded that there are effects of the use of hand puppet media on the storytelling skills of Grade V students of elementary schools in Cluster 4 of Bantul District. Keywords: hand puppet media, storytelling skills